2011
DOI: 10.1136/bmjopen-2011-000328
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised controlled trial of a comprehensive accreditation intervention to reduce alcohol consumption at community sports clubs: study protocol: Figure 1

Melanie Kingsland,
Luke Wolfenden,
Bosco C Rowland
et al.

Abstract: IntroductionExcessive alcohol consumption is responsible for considerable harm from chronic disease and injury. Within most developed countries, members of sporting clubs consume alcohol at levels above that of communities generally. Despite the potential benefits of interventions to address alcohol consumption in sporting clubs, there have been no randomised controlled trials to test the effectiveness of these interventions. The aim of this study is to examine the effectiveness of a comprehensive accreditatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…Several other authors have suggested sports-based interventions programs for specific groups, including high school students [7,8,42,43]. Our study results suggest the need to consider the associated aspects of sports practice such as motivation, frequency and especially the culture, for intervention programs among this population.…”
Section: Discussionmentioning
confidence: 59%
“…Several other authors have suggested sports-based interventions programs for specific groups, including high school students [7,8,42,43]. Our study results suggest the need to consider the associated aspects of sports practice such as motivation, frequency and especially the culture, for intervention programs among this population.…”
Section: Discussionmentioning
confidence: 59%
“…Estrategias como el programa de acreditación de clubes Good Sports (29,30) parecen ser prometedoras en reducir el consumo de alcohol en los miembros de los clubes deportivos, y pueden ser eventualmente replicadas en Latinoamérica, una vez se adapten y establezca su eficacia a través de ensayos aleatorios controlados.…”
Section: Discussionunclassified
“…A repeat cross‐sectional, parallel group cluster randomised controlled trial was undertaken, with community football clubs (clusters) randomised to either a control or an intervention group. The primary outcomes were: risky drinking at the sporting club and overall alcohol‐consumption related harm regardless of drinking setting 24 . A secondary trial outcome was the effect of the intervention on social capital, measured by the constructs of safety and participation.…”
Section: Methodsmentioning
confidence: 99%